LEARNING THEORY ACCORDING TO HUMANISTIC PSYCHOLOGY AND ITS IMPLEMENTATION IN STUDENTS - Putri, Nurul Hanifah; Yusuf, Arbaiyah; Prayuga, Nabila Grresita Aulyana Putri; Syafira, Nabilla Puteri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2024)
This research describes learning theory according to Humanistic Psychology and its implementation. Through the application of library research or library research (study) methods, the implementation of this research begins with problem formulation, focus preparation, study and then reading various reference libraries sourced from e-journals and digital books by understanding and studying them seriously until reaching the writing and organizing process. material. The research results show that humanistic learning theory places great emphasis on the importance of the content of a series of learning activities. The aim of learning according to humanistic theory is to make people more humane. Students are expected to be independent, brave, and not constrained by other people's opinions. They are also expected to manage their personality responsibly while adhering to all rules, norms, discipline, and ethical standards. Thus, the integration of humanistic psychology into education can help students understand themselves as humans.